PROTECTION OF HUMAN RIGHTS OF ILLEGAL MIGRANT WORKERS: AN INTERNATIONAL LEGAL PERSPECTIVE - Rani Salsabila Dalimunthe; Harisman (RADJA PUBLIKA, 2026)
The increase in international migration has led to a growing number of migrant workers in irregular or illegal situations, especially from developing countries such as Indonesia. In reality, illegal migrant workers are often seen solely as violators of immigration laws, so their presence is often associated with repressive actions such as detention and deportation. In addition, the presence of illegal migrant workers often creates vulnerabilities, including exploitation, discrimination, human trafficking, and limited access to justice. This study aims to analyze the understanding of human rights protection for illegal migrant workers and state responsibilities in the context of international law. The method used in this study is normative legal research with a legislative and conceptual approach, through an analysis of international legal instruments such as the Universal Declaration of Human Rights, ICCPR, ICESCR, and ILO Convention No. 143 of 1975. The research findings show that illegal migration status does not eliminate the basic rights of migrant workers as individuals with human rights. The state is responsible for respecting, protecting, and fulfilling the rights of illegal migrant workers without discrimination. This protection includes the right to decent working conditions, fair wages, protection from exploitation, and access to justice. Therefore, migration policies based on human rights and alignment of national laws with international legal standards are needed to ensure humane and fair protection for irregular migrant workers.